2014
DOI: 10.5301/hipint.5000132
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ion Release: Also a Concern for Ceramic-on-Ceramic Couplings?

Abstract: BIOLOX delta is the newest ceramic composite material of the BIOLOX family and its use in hip devices represents a good alternative to Metal-on-Metal or Metal-on-Polyethylene coupling. Some Metal-on-Metal hip devices have shown chromium and cobalt release, which promoted toxic effects. Furthermore, the ceramic composite contains trivalent chromium, even if strongly bound to the alumina lattice. The present study is aimed at detecting any 'in vivo' release of chromium ions from BIOLOX delta bearings in the bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…Enhanced mechanical properties increase the durability of the ceramic and allow greater design freedom. In particular, the use of large diameter femoral head components should reduce the risk of dislocation without changing neck diameter, improve stem mobility, and reduce the risk of impingement between the rim of the liner or cup and the neck of the stem (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enhanced mechanical properties increase the durability of the ceramic and allow greater design freedom. In particular, the use of large diameter femoral head components should reduce the risk of dislocation without changing neck diameter, improve stem mobility, and reduce the risk of impingement between the rim of the liner or cup and the neck of the stem (12).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, large diameter ceramic heads might have higher wear rates. Hajjar et al (12) assessed the effect of increasing head size on the wear of Biolox®delta CoC bearings. Under microseparation using edge loading conditions, the wear rate of 36 mm bearings (0.22 mm 3 /million cycles) was greater than that of 28 mm bearings (0.13 mm 3 /million cycles), but the wear rate of Biolox Delta COC bearings under microseparation conditions was still very low (<0.25 mm 3 /million cycles) compared to earlier generation COC bearings (Biolox®forte, 1.84 mm 3 /million cycles) and other bearing materials such as MoM bearings (2-8 mm 3 /million cycles).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, as far as the lack of effect of circulating Cr on HMOX-1 induction is concerned, this is probably due to the fact that only Cr (III) was circulating and does not appear to exert any direct effect on HMOX-1 (43). Previous studies (47,48), have demonstrated that the Cr released by MoM prostheses and present in circulation is in the Cr (III) form. This was confirmed by preliminary evaluations of a small group of samples, in which the chemical speciation was determined by hyphenated techniques (HPLC-ICP-MS), investigating the concentration of Cr (III) and Cr (VI) in the synovial fluid of patients with prostheses, confirming that the only species present is Cr (III) (unpublished data from Laboratory of Toxicology and Industrial Hygiene, University of Brescia, Italy).…”
Section: Discussionmentioning
confidence: 95%
“…However, cobalt is missing from large-head CoC bearings and studies have shown lower fretting and corrosion scores, 5 low titanium ion levels and low Chromium levels with ceramic heads used with or without a titanium alloy sleeve. 21,22 In conclusion, new technology should be introduced on the market cautiously. This is especially true for the preassembled large diameter ceramic monoblock acetabular component used in this study since it resembled the acetabular component used with large-head MoM THA.…”
Section: Discussionmentioning
confidence: 99%